The Linguistic Landscape in Lovina, Bali: A Sociolinguistic of Globalization Perspective - Putu Stefy Adnyaswari; I Made Suta Paramarta; I Wayan Swandana (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study examines the linguistic landscape of Lovina, Bali, from a sociolinguistic globalization perspective by analyzing language scales, indexical meanings, and polycentric norms in public signage. As a tourism destination, Lovina represents a multilingual space where global, national, and local languages interact through commercial and public signs. This research used a qualitative descriptive approach involving 100 public signs collected from tourism-related areas, including hotels, restaurants, cafés, travel agencies, souvenir shops, and public facilities. Data were collected through photographic documentation and observation, then analyzed through organization, coding, categorization, interpretation, and contextual analysis. The findings indicate that English has the highest visibility as a global linguistic resource related to tourism, international communication, and economic value. Indonesian remains important as a national language supporting accessibility and public communication, while Balinese represents local identity and cultural authenticity. The study reveals that public signs convey social identity, economic orientation, and cultural meanings. Moreover, the linguistic landscape reflects polycentricity through negotiations among global tourism demands, national language norms, and local cultural values. The findings emphasize the role of linguistic landscapes as social and cultural representations and as resources for English language education, particularly English for Specific Purposes, Critical Language Awareness, and multimodal literacy development.